Chromosome 1q21 gain is an adverse prognostic factor for newly diagnosed multiple myeloma patients treated with bortezomib-based regimens - Liu, Xiao; Jia, Shuangshuang; Chu, Yuping; Tian, Biao; Gao, Yaya; Zhang, Chunyan; Zheng, Yanhua; Jia, Weijing; Liu, Xiangxiang; Yuan, Ruifeng; Zhang, Na; Feng, Juan; et al. (Frontiers in Oncology, 2022)
Chromosome 1q21 aberrations is one of the most common cytogenetic abnormalities in multiple myeloma, which is considered to be an important prognostic factor and clinical index. The present study analyzed the clinical relevance and prognostic impact of 1q21 gain in 180 patients with newly diagnosed multiple myeloma treated with Bortezomib-based regimen. We found that 47.2% (85 / 180) patients detected 1q21 gain, and patients with 1q21 gain had a worse prognosis. Strikingly, our results showed that excluding the effects of other genetic coexistence, patients carried at least 4 copies of 1q21 gain led to worse survival. Moreover, del(13q) has a strong correlation with 1q21 gain, and the coexistence of del(13q) and 1q21 gain play an important role in reducing PFS and OS. Therefore, gain of 1q21 should be considered as a high-risk feature in patients with multiple myeloma treated with Bortezomib-based regimen.